Graphene modified ABS nano-wire for 3D printing and preparation method of graphene modified ABS nano-wire
By introducing nanographene-coated whisker reinforcer into ABS wires for 3D printing, the problem of insufficient thermal conductivity and strength of ABS wires is solved, and higher mechanical strength and thermal conductivity are achieved, which is suitable for high temperature and high mechanical stress application scenarios.
Patent Information
- Application Number
- CN202510385964.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing ABS wires for 3D printing have poor thermal conductivity and their strength needs to be further improved, making it difficult to meet the performance requirements in high temperature and high mechanical stress application scenarios.
Graphene-modified ABS nanowires were prepared by introducing nanographene-coated whisker reinforcement into the ABS matrix and stirring and melt extrusion using a specific preparation method.
It significantly enhances the overall mechanical strength and thermal conductivity of ABS wires, making 3D printed parts have high strength and high heat dissipation efficiency, and is suitable for making 3D printed parts that require high strength and high temperature resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of 3D printing materials, and in particular to a graphene-modified ABS nanowire for 3D printing and a preparation method thereof. Background Art
[0002] As a rapid prototyping technology, 3D printing technology has developed rapidly in recent years. With the rapid development of 3D printing technology, the selection and performance of materials have become one of the key factors affecting the quality and efficiency of printed products.
[0003] Acrylonitrile-butadiene-styrene (ABS), as a common thermoplastic, is widely used in the field of 3D printing due to its good processability, toughness, surface gloss and impact resistance. However, the thermal conductivity of traditional ABS materials is poor, and its strength needs to be further improved, which limits its application in some fields with high requirements for thermal conductivity and strength, especially in application scenarios that need to withstand high temperatures and high mechanical stresses. Its performance is often insufficient to meet the requirements. Therefore, the development of a graphene-modified ABS nanowire for 3D printing and its preparation method is of great significance for improving the comprehensive performance of 3D printed parts. Summary of the invention
[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a graphene-modified ABS nanowire for 3D printing and a preparation method thereof, which solves the problem that the existing ABS wire for 3D printing has poor thermal conductivity and the strength needs to be further improved. In application scenarios that need to withstand high temperature and high mechanical stress, its performance is often insufficient to meet the requirements.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A graphene-modified ABS nanowire for 3D printing, comprising the following components in parts by weight: 85-90 parts of ABS resin, 0.5-7.5 parts of nanographene-coated whisker reinforcing agent, 2-8 parts of dioctyl terephthalate, 0.1-0.3 parts of calcium stearate, 0.3-0.5 parts of vinyl bisstearic acid amide and 0.07-0.11 parts of antioxidant; Wherein, the nanographene-coated whisker reinforcing agent is prepared by the following steps: Step s1: add eugenol, sodium hydroxide and deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 0-5°C and a stirring rate of 300-400r / min, then add succinyl chloride solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, continue to stir and react for 1-2 hours, then heat to 25-30°C and continue to stir and react for 2-3 hours. After the reaction is completed, let the reaction product stand for separation, wash the organic phase with sodium hydroxide solution and distilled water for 3-5 times in sequence, then dry with anhydrous magnesium sulfate, and then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain a diene intermediate; Step s2: Add the diene intermediate, Karstedt catalyst and anhydrous toluene to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 50-55°C and continue to stir and react for 20-30 minutes, then add triethoxysilane dropwise while stirring, control the dropping rate to 1-2 drops / s, continue to stir and react for 1-2 hours after the dropwise addition is completed, then heat to 75-80°C and continue to stir and react for 7-8 hours, filter the reaction product while hot after the reaction is completed, then cool the filtrate to room temperature, and then rotary evaporate to remove the solvent to obtain a double-end modified coupling agent; Step s3: adding graphite powder and concentrated sulfuric acid to a three-necked flask equipped with an agitator and a thermometer, stirring the reaction for 30-40 minutes at a temperature of 0-5°C and a stirring rate of 300-400r / min, then adding sodium nitrate and potassium permanganate and continuing to stir the reaction for 2-3 hours, then heating the temperature to 40-45°C and continuing to stir the reaction for 1-2 hours, then adding deionized water and heating the temperature to 85-95°C and continuing to stir the reaction for 20-30 minutes, after the reaction is completed, the reaction product is cooled to room temperature, then poured into a hydrogen peroxide solution, then centrifuged, the precipitate is washed with distilled water for 3-5 times, then placed in a vacuum drying oven, and dried at a temperature of 50-55°C for 2-3 hours to obtain nano graphene oxide; Step s4: Add nano-graphene oxide, silicon carbide whiskers and deionized water to a three-necked flask equipped with an agitator, a thermometer and a constant pressure dropping funnel, perform ultrasonic treatment at an ultrasonic frequency of 45-55kHz for 1-2h, then adjust the pH to 8-9 with ammonia water, and then stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 10-15min, then heat the temperature to 70-75°C and continue to stir the reaction for 10-15min, then add the double-end modified linker solution dropwise while stirring, control the dropping rate to 1-2 drops / s, and continue to stir the reaction for 6-8h after the dropwise addition is completed. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with anhydrous ethanol for 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 50-55°C for 3-5h to obtain a nano-graphene coated whisker reinforcing agent.
[0006] As a further solution of the present invention: the usage ratio of the eugenol, sodium hydroxide, deionized water and succinyl chloride solution in step s1 is 20-25 mmol: 25-30 mmol: 40-50 mL: 20-22 mL.
[0007] As a further solution of the present invention: the succinyl chloride solution in step s1 is a solution formed by dissolving succinyl chloride in ethyl acetate at a ratio of 10 mmol:20 mL, and the mass fraction of the sodium hydroxide solution is 5%.
[0008] As a further solution of the present invention: the usage ratio of the diene intermediate, Karstedt catalyst, anhydrous toluene and triethoxysilane in step S2 is 10 mmol: 0.1-0.3 g: 80-100 mL: 20 mmol.
[0009] As a further solution of the present invention: the usage ratio of the graphite powder, concentrated sulfuric acid, sodium nitrate, potassium permanganate and deionized water in step s3 is 3g:100-120mL:2-3g:13-15g:90-100mL.
[0010] As a further solution of the present invention: the mass fraction of the concentrated sulfuric acid in step s3 is 98%; the mass fraction of the hydrogen peroxide solution is 25-30%.
[0011] As a further solution of the present invention: the usage ratio of the nano-graphene oxide, silicon carbide whiskers, deionized water and double-ended modified linker solution in step s4 is 0.8-3.6 g: 10 g: 100-120 mL: 20-25 mL.
[0012] As a further solution of the present invention: the CAS number of the silicon carbide whisker in step s4 is 409-21-2 and the average particle size is 100-500nm; the double-ended modified linker solution is a solution formed by dissolving the double-ended modified linker in anhydrous ethanol at a ratio of 1.2-2.8g:10mL, and the mass fraction of the ammonia water is 25%.
[0013] As a further solution of the present invention: a method for preparing graphene-modified ABS nanowires for 3D printing, comprising the following steps: Step 1: weigh 85-90 parts of ABS resin, 0.5-7.5 parts of nanographene-coated whisker reinforcement, 2-8 parts of dioctyl terephthalate, 0.1-0.3 parts of calcium stearate, 0.3-0.5 parts of vinyl bisstearamide and 0.07-0.11 parts of antioxidant according to weight parts, and set aside; Step 2: Add ABS resin, nanographene-coated whisker reinforcement, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stir and mix for 30-40 minutes at a temperature of 40-50° C. and a stirring rate of 300-400 r / min to obtain a mixture; Step 3: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220°C, zone 2 to 230°C, zone 3 to 230°C, zone 4 to 240°C, zone 5 to 240°C and zone 6 to 245°C, and melt-extrude at a screw speed of 80-120r / min, and obtain wire pellets after cooling, drying and pelletizing; Step 4: Add the wire pellets into a single screw extruder and extrude them at a temperature of 220-240° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.70-1.75 mm.
[0014] As a further solution of the present invention: the model of the ABS resin is ABS PA-757K; the model of the antioxidant is one of antioxidant 1076, antioxidant 1035 and antioxidant 1010.
[0015] Beneficial effects of the present invention: The invention discloses a graphene-modified ABS nanowire for 3D printing and a preparation method thereof. The invention comprises the following steps: stirring and mixing ABS resin, a nanographene-coated whisker reinforcing agent, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and an antioxidant to obtain a mixture, melting and extruding the mixture, cooling, drying and pelletizing to obtain wire pellets, and extruding and molding the wire pellets to obtain the graphene-modified ABS nanowire for 3D printing. The preparation method introduces the nanographene-coated whisker reinforcing agent as a nano-reinforced phase into an ABS matrix, thereby significantly enhancing the overall mechanical strength and thermal conductivity of the ABS wire. During the printing process, the ABS wire can provide excellent mechanical properties and heat dissipation capacity, so that the 3D printed part has high strength and high heat dissipation efficiency, is suitable for making 3D printed parts requiring high strength and high temperature resistance, and is suitable for application scenarios with high performance requirements, so that the application range of 3D printing technology is wider. Moreover, the ABS wire has a simple process, is convenient to operate, and is easy to realize industrialized production.
[0016] In the process of preparing graphene-modified ABS nanowires for 3D printing, a nanographene-coated whisker reinforcing agent is first prepared. First, eugenol and succinyl chloride are reacted. The hydroxyl group on eugenol reacts with the acyl chloride group on succinyl chloride to form a diene intermediate containing two alkenyl groups. Then, the diene intermediate reacts with triethoxysilane. The alkenyl group on the diene intermediate reacts with the Si-H on the triethoxysilane to undergo a silylation reaction. A large amount of siloxane is introduced to obtain a double-end modified linker. Then, graphite powder is used as a raw material to prepare nanographene oxide. The invention relates to a method for preparing nano graphene oxide and silicon carbide whiskers by using a double-ended modified linker. The siloxane on the double-ended modified linker is hydrolyzed to form silanol, which is then grafted onto the surface of the nano graphene oxide and silicon carbide whiskers. The nano graphene oxide is then tightly linked to the surface of the silicon carbide whiskers, thereby wrapping them to obtain a nano graphene-coated whisker reinforcing agent. The nano graphene oxide shell on the surface of the silicon carbide whiskers reduces the surface energy between the silicon carbide whiskers and reduces the occurrence of agglomeration. At the same time, the use of the double-ended modified linker further improves the carbonization The compatibility of the composite reinforcement of silicon whisker-nanographene oxide and ABS matrix enables the composite reinforcement to be evenly dispersed in the ABS matrix, ensuring the performance stability and consistency of the ABS material. In addition, the silicon carbide whisker itself has high strength and high modulus, and can bear most of the external force load, thereby improving the overall strength of the ABS material. After being coated with nanographene oxide, the contact area between the silicon carbide whisker and the ABS matrix can be increased, and the stress transfer efficiency can be improved. When external force acts on the ABS material, the stress can be more effectively transferred from the matrix to the silicon carbide whisker, giving full play to the reinforcing effect of the silicon carbide whisker. Moreover, when cracks appear in the material, the nanographene oxide sheet can bridge the two ends of the crack, and consume the energy required for crack expansion through its own deformation and stretching, thereby improving the ABS material's ability to resist crack expansion, and then enhancing the strength of the ABS material. At the same time, silicon carbide whiskers and nanographene oxide both have ultra-high thermal conductivity. After the two are combined, they can form a rich and continuous high-efficiency heat conduction channel, so that heat can be quickly transferred, significantly improving the thermal conductivity of the ABS material. Therefore, the introduction of nano-graphene-coated whisker reinforcement enables ABS material to have excellent thermal conductivity while maintaining good mechanical properties. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Embodiment 1: This embodiment is a method for preparing graphene-modified ABS nanowires for 3D printing, comprising the following steps: Step S1: 20mmol eugenol, 25mmol sodium hydroxide and 40mL deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 0°C and a stirring rate of 300r / min for 20min, and then 20mL of succinyl chloride solution formed by dissolving 10mmol:20mL of ethyl acetate in dropwise addition while stirring, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the stirring reaction is continued for 1h, and then the temperature is raised to 25°C and the stirring reaction is continued for 2h. After the reaction is completed, the reaction product is allowed to stand for separation, and the organic phase is washed three times with a sodium hydroxide solution with a mass fraction of 5% and distilled water in sequence, and then dried with anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene intermediate; Step S2: 10 mmol of diene intermediate, 0.1 g of Karstedt catalyst and 80 mL of anhydrous toluene were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The reaction was stirred for 20 min at a temperature of 25° C. and a stirring rate of 300 r / min, and then the temperature was raised to 50° C. and the stirring reaction was continued for 20 min. Then, 20 mmol of triethoxysilane was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the stirring reaction was continued for 1 h, and then the temperature was raised to 75° C. and the stirring reaction was continued for 7 h. After the reaction was completed, the reaction product was filtered while hot, and then the filtrate was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a double-end modified coupling agent; Step S3: 3 g of graphite powder and 100 mL of concentrated sulfuric acid with a mass fraction of 98% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 0°C and a stirring rate of 300 r / min for 30 min, then 2 g of sodium nitrate and 13 g of potassium permanganate are added and stirred for reaction for 2 h, then the temperature is raised to 40°C and the stirring reaction is continued for 1 h, then 90 mL of deionized water is added and the temperature is raised to 85°C and the stirring reaction is continued for 20 min, after the reaction is completed, the reaction product is cooled to room temperature, and then poured into a hydrogen peroxide solution with a mass fraction of 25%, and then centrifuged, the precipitate is washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 50°C for 2 h to obtain nano graphene oxide; Step S4: 0.8 g of nano-graphene oxide, 10 g of silicon carbide whiskers with a CAS number of 409-21-2 and an average particle size of 500 nm, and 100 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a constant pressure dropping funnel, and ultrasonically treated for 1 h at an ultrasonic frequency of 45 kHz, and then adjusted to pH 8 with 25% ammonia water, and then stirred for 10 min at a temperature of 25 ° C and a stirring rate of 300 r / min, and then heated to The reaction was continued under stirring at 70°C for 10 minutes, and then 20 mL of a double-end modified coupling agent solution formed by dissolving the double-end modified coupling agent in anhydrous ethanol at a ratio of 1.2 g:10 mL was added dropwise while stirring, and the drop rate was controlled to be 1 drop / s. After the dropwise addition was completed, the reaction was continued under stirring for 6 hours. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 50°C for 3 hours to obtain a nanographene-coated whisker reinforcement. Step S5: 85 parts of ABS resin with a model number of ABS PA-757K, 0.5 parts of nanographene-coated whisker reinforcing agent, 2 parts of dioctyl terephthalate, 0.1 parts of calcium stearate, 0.3 parts of vinyl bisstearic acid amide and 0.07 parts of antioxidant with a model number of antioxidant 1076 are weighed according to weight parts and set aside; Step S6: adding ABS resin, nanographene-coated whisker reinforcement, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stirring and mixing for 30 minutes at a temperature of 40° C. and a stirring rate of 300 r / min to obtain a mixture; Step S7: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220° C., zone 2 to 230° C., zone 3 to 230° C., zone 4 to 240° C., zone 5 to 240° C., and zone 6 to 245° C., and melt-extrude the mixed material at a screw speed of 80 r / min, and obtain wire pellets after cooling, drying, and pelletizing; Step S8: Add the wire pellets into a single screw extruder and extrude them at a temperature of 220° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.75 mm.
[0019] Embodiment 2: This embodiment is a method for preparing graphene-modified ABS nanowires for 3D printing, comprising the following steps: Step S1: 22mmol eugenol, 28mmol sodium hydroxide and 45mL deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The reaction is stirred for 25min at a temperature of 3°C and a stirring rate of 350r / min, and then 21mL of succinyl chloride is added dropwise while stirring. The succinyl chloride solution formed by dissolving 10mmol:20mL in ethyl acetate is added dropwise, and the dropping rate is controlled to be 1 drop / s. After the addition is completed, the reaction is continued to be stirred for 1.5h, and then the temperature is raised to 28°C and the reaction is continued to be stirred for 2.5h. After the reaction is completed, the reaction product is allowed to stand for separation, and the organic phase is washed 4 times with a sodium hydroxide solution with a mass fraction of 5% and distilled water in sequence, and then dried with anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene intermediate; Step S2: 10 mmol of diene intermediate, 0.2 g of Karstedt catalyst and 90 mL of anhydrous toluene were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The reaction was stirred for 25 min at a temperature of 28° C. and a stirring rate of 350 r / min, and then the temperature was raised to 52° C. and the stirring reaction was continued for 25 min. Then, 20 mmol of triethoxysilane was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the stirring reaction was continued for 1.5 h, and then the temperature was raised to 78° C. and the stirring reaction was continued for 7.5 h. After the reaction was completed, the reaction product was filtered while hot, and then the filtrate was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a double-end modified coupling agent; Step S3: 3 g of graphite powder and 110 mL of concentrated sulfuric acid with a mass fraction of 98% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 3° C. and a stirring rate of 350 r / min for 35 min, then 2.5 g of sodium nitrate and 14 g of potassium permanganate are added and stirred for reaction for 2.5 h, then the temperature is raised to 42° C. and the stirring reaction is continued for 1.5 h, then 95 mL of deionized water is added and the temperature is raised to 90° C. and the stirring reaction is continued for 25 min, after the reaction is completed, the reaction product is cooled to room temperature, and then poured into a hydrogen peroxide solution with a mass fraction of 28%, and then centrifuged, the precipitate is washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 52° C. for 2.5 h to obtain nano graphene oxide; Step S4: 2.2 g of nano-graphene oxide, 10 g of silicon carbide whiskers with a CAS number of 409-21-2 and an average particle size of 500 nm, and 110 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a constant pressure dropping funnel, and ultrasonically treated for 1.5 h at an ultrasonic frequency of 50 kHz, and then adjusted to pH 8.5 with 25% ammonia water, and then stirred for 12 min at a temperature of 28 ° C and a stirring rate of 350 r / min, and then The mixture was heated to 72°C and stirred for 12 minutes. Then, 22 mL of a double-end modified coupling agent solution prepared by dissolving the double-end modified coupling agent in anhydrous ethanol at a ratio of 2 g:10 mL was added dropwise while stirring. The drop rate was controlled to be 1 drop / s. After the addition was completed, the mixture was stirred for 7 hours. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 4 times and then placed in a vacuum drying oven. The mixture was dried at 52°C for 4 hours to obtain a nanographene-coated whisker reinforcing agent. Step S5: 88 parts of ABS resin with a model number of ABS PA-757K, 4 parts of nanographene-coated whisker reinforcing agent, 5 parts of dioctyl terephthalate, 0.2 parts of calcium stearate, 0.4 parts of vinyl bisstearamide and 0.09 parts of antioxidant with a model number of antioxidant 1035 are weighed according to weight parts and set aside; Step S6: adding ABS resin, nanographene-coated whisker reinforcement, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stirring and mixing for 35 minutes at a temperature of 45° C. and a stirring rate of 350 r / min to obtain a mixture; Step S7: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220° C., zone 2 to 230° C., zone 3 to 230° C., zone 4 to 240° C., zone 5 to 240° C., and zone 6 to 245° C., and melt-extrude the mixed material at a screw speed of 100 r / min, and obtain wire pellets after cooling, drying, and pelletizing; Step S8: Add the wire pellets into a single screw extruder and extrude them at a temperature of 230° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.75 mm.
[0020] Embodiment 3: This embodiment is a method for preparing graphene-modified ABS nanowires for 3D printing, comprising the following steps: Step S1: 25mmol eugenol, 30mmol sodium hydroxide and 50mL deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 5°C and a stirring rate of 400r / min for 30min, and then 22mL of succinyl chloride solution formed by dissolving 10mmol:20mL of ethyl acetate in dropwise addition while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 2h, and then the temperature is raised to 30°C and the stirring reaction is continued for 3h. After the reaction is completed, the reaction product is allowed to stand for separation, and the organic phase is washed 5 times with a sodium hydroxide solution and distilled water with a mass fraction of 5% in sequence, and then dried with anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene intermediate; Step S2: 10 mmol of diene intermediate, 0.3 g of Karstedt catalyst and 100 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 55° C. and the stirring reaction is continued for 30 min. Then, 20 mmol of triethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the stirring reaction is continued for 2 h, and then the mixture is heated to 80° C. and the stirring reaction is continued for 8 h. After the reaction is completed, the reaction product is filtered while hot, and then the filtrate is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain a double-end modified coupling agent; Step S3: 3 g of graphite powder and 120 mL of concentrated sulfuric acid with a mass fraction of 98% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 5° C. and a stirring rate of 400 r / min for 40 min, then 3 g of sodium nitrate and 15 g of potassium permanganate are added and stirred for reaction for 3 h, then the temperature is raised to 45° C. and the stirring reaction is continued for 2 h, then 100 mL of deionized water is added and the temperature is raised to 95° C. and the stirring reaction is continued for 30 min, after the reaction is completed, the reaction product is cooled to room temperature, and then poured into a hydrogen peroxide solution with a mass fraction of 30%, and then centrifuged, the precipitate is washed with distilled water 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 55° C. for 3 h to obtain nano graphene oxide; Step S4: 3.6 g of nano-graphene oxide, 10 g of silicon carbide whiskers with a CAS number of 409-21-2 and an average particle size of 500 nm, and 120 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, and a constant pressure dropping funnel, and ultrasonically treated for 2 h at an ultrasonic frequency of 55 kHz, and then adjusted to pH 9 with 25% ammonia water, and then stirred for 15 min at a temperature of 30 ° C and a stirring rate of 400 r / min, and then heated to The reaction was continued under stirring at 75°C for 15 minutes, and then 25 mL of a double-end modified coupling agent solution formed by dissolving 2.8 g:10 mL of a double-end modified coupling agent in anhydrous ethanol was added dropwise while stirring, and the drop rate was controlled to be 2 drops / s. After the dropwise addition was completed, the reaction was continued under stirring for 8 hours. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 55°C for 5 hours to obtain a nanographene-coated whisker reinforcement. Step S5: 90 parts of ABS resin with a model number of ABS PA-757K, 7.5 parts of nanographene-coated whisker reinforcing agent, 8 parts of dioctyl terephthalate, 0.3 parts of calcium stearate, 0.5 parts of vinyl bisstearic acid amide and 0.11 parts of antioxidant with a model number of antioxidant 1010 are weighed according to weight parts and set aside; Step S6: adding ABS resin, nanographene-coated whisker reinforcement, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stirring and mixing at a temperature of 50° C. and a stirring rate of 400 r / min for 40 minutes to obtain a mixture; Step S7: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220° C., zone 2 to 230° C., zone 3 to 230° C., zone 4 to 240° C., zone 5 to 240° C., and zone 6 to 245° C., and melt-extrude the mixed material at a screw speed of 120 r / min, and obtain wire pellets after cooling, drying, and pelletizing; Step S8: Add the wire pellets into a single screw extruder and extrude them at a temperature of 240° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.75 mm.
[0021] Comparative Example 1: This comparative example is a method for preparing graphene-modified ABS nanowires for 3D printing, comprising the following steps: Step S1: 90 parts of ABS resin (model ABS PA-757K), 8 parts of dioctyl terephthalate, 0.3 parts of calcium stearate, 0.5 parts of vinyl bisstearamide and 0.11 parts of antioxidant (model Antioxidant 1010) were weighed and set aside; Step S2: adding ABS resin, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stirring and mixing at a temperature of 50° C. and a stirring rate of 400 r / min for 40 minutes to obtain a mixture; Step S3: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220° C., zone 2 to 230° C., zone 3 to 230° C., zone 4 to 240° C., zone 5 to 240° C., and zone 6 to 245° C., and melt-extrude the mixed material at a screw speed of 120 r / min, and obtain wire pellets after cooling, drying, and pelletizing; Step S4: adding the wire pellets into a single screw extruder, and extruding them at a temperature of 240° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.75 mm.
[0022] Comparative Example 2: This comparative example is a method for preparing graphene-modified ABS nanowires for 3D printing, comprising the following steps: Step S1: 3g of graphite powder and 120mL of concentrated sulfuric acid with a mass fraction of 98% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 5°C and a stirring rate of 400r / min for 40min, then 3g of sodium nitrate and 15g of potassium permanganate are added and stirred for reaction for 3h, then the temperature is raised to 45°C and the stirring reaction is continued for 2h, then 100mL of deionized water is added and the temperature is raised to 95°C and the stirring reaction is continued for 30min, after the reaction is completed, the reaction product is cooled to room temperature, then poured into a hydrogen peroxide solution with a mass fraction of 30%, and then centrifuged, the precipitate is washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 55°C for 3h to obtain nano graphene oxide; Step S2: 3.6 g of nano-graphene oxide, 10 g of silicon carbide whiskers with a CAS number of 409-21-2 and an average particle size of 500 nm, and 120 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, and a constant pressure dropping funnel, and ultrasonically treated for 2 h at an ultrasonic frequency of 55 kHz, and then adjusted to pH 9 with 25% ammonia water by mass, and then stirred for 15 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then heated to 75° C. and continued to stir for 8 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filter cake is washed with anhydrous ethanol 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 55° C. for 5 h to obtain a nano-graphene-coated whisker reinforcing agent; Step S3: 90 parts of ABS resin with a model number of ABS PA-757K, 7.5 parts of nanographene-coated whisker reinforcing agent, 8 parts of dioctyl terephthalate, 0.3 parts of calcium stearate, 0.5 parts of vinyl bisstearamide and 0.11 parts of antioxidant with a model number of antioxidant 1010 are weighed according to weight parts and set aside; Step S4: adding ABS resin, nano-graphene-coated whisker reinforcement, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stirring and mixing at a temperature of 50° C. and a stirring rate of 400 r / min for 40 minutes to obtain a mixture; Step S5: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220° C., zone 2 to 230° C., zone 3 to 230° C., zone 4 to 240° C., zone 5 to 240° C., and zone 6 to 245° C., and melt-extrude the mixed material at a screw speed of 120 r / min, and obtain wire pellets after cooling, drying, and pelletizing; Step S6: Add the wire pellets into a single screw extruder and extrude them at a temperature of 240° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.75 mm.
[0023] Comparative Example 3: This comparative example is a method for preparing graphene-modified ABS nanowires for 3D printing, comprising the following steps: Step S1: 25mmol eugenol, 30mmol sodium hydroxide and 50mL deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 5°C and a stirring rate of 400r / min for 30min, and then 22mL of succinyl chloride solution formed by dissolving 10mmol:20mL of ethyl acetate in dropwise addition while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 2h, and then the temperature is raised to 30°C and the stirring reaction is continued for 3h. After the reaction is completed, the reaction product is allowed to stand for separation, and the organic phase is washed 5 times with a sodium hydroxide solution and distilled water with a mass fraction of 5% in sequence, and then dried with anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene intermediate; Step S2: 10 mmol of diene intermediate, 0.3 g of Karstedt catalyst and 100 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 55° C. and the stirring reaction is continued for 30 min. Then, 20 mmol of triethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the stirring reaction is continued for 2 h, and then the mixture is heated to 80° C. and the stirring reaction is continued for 8 h. After the reaction is completed, the reaction product is filtered while hot, and then the filtrate is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain a double-end modified coupling agent; Step S3: 3 g of graphite powder and 120 mL of concentrated sulfuric acid with a mass fraction of 98% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 5° C. and a stirring rate of 400 r / min for 40 min, then 3 g of sodium nitrate and 15 g of potassium permanganate are added and stirred for reaction for 3 h, then the temperature is raised to 45° C. and the stirring reaction is continued for 2 h, then 100 mL of deionized water is added and the temperature is raised to 95° C. and the stirring reaction is continued for 30 min, after the reaction is completed, the reaction product is cooled to room temperature, and then poured into a hydrogen peroxide solution with a mass fraction of 30%, and then centrifuged, the precipitate is washed with distilled water 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 55° C. for 3 h to obtain nano graphene oxide; Step S4: 3.6 g of nano-graphene oxide and 120 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and ultrasonically treated for 2 h at an ultrasonic frequency of 55 kHz, and then adjusted to pH 9 with 25% ammonia water by mass, and then stirred for 15 min at a temperature of 30 ° C and a stirring rate of 400 r / min, and then heated to 75 ° C and continued to stir for 15 min, and then added dropwise while stirring 25 mL of a double-ended modified linker solution formed by dissolving 2.8 g:10 mL of a double-ended modified linker in anhydrous ethanol, and the dropping rate is controlled to 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 8 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, the filter cake is washed with anhydrous ethanol 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 55 ° C for 5 h to obtain a modified nano-graphene enhancer; Step S5: 90 parts of ABS resin with a model number of ABS PA-757K, 7.5 parts of modified nano-graphene reinforcing agent, 8 parts of dioctyl terephthalate, 0.3 parts of calcium stearate, 0.5 parts of vinyl bisstearic acid amide and 0.11 parts of antioxidant with a model number of antioxidant 1010 are weighed according to weight parts and set aside; Step S6: adding ABS resin, modified nano-graphene reinforcing agent, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stirring and mixing for 40 minutes at a temperature of 50° C. and a stirring rate of 400 r / min to obtain a mixture; Step S7: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220° C., zone 2 to 230° C., zone 3 to 230° C., zone 4 to 240° C., zone 5 to 240° C., and zone 6 to 245° C., and melt-extrude the mixed material at a screw speed of 120 r / min, and obtain wire pellets after cooling, drying, and pelletizing; Step S8: Add the wire pellets into a single screw extruder and extrude them at a temperature of 240° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.75 mm.
[0024] Comparative Example 4: This comparative example is a method for preparing graphene-modified ABS nanowires for 3D printing, comprising the following steps: Step S1: 25mmol eugenol, 30mmol sodium hydroxide and 50mL deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 5°C and a stirring rate of 400r / min for 30min, and then 22mL of succinyl chloride solution formed by dissolving 10mmol:20mL of ethyl acetate in dropwise addition while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 2h, and then the temperature is raised to 30°C and the stirring reaction is continued for 3h. After the reaction is completed, the reaction product is allowed to stand for separation, and the organic phase is washed 5 times with a sodium hydroxide solution and distilled water with a mass fraction of 5% in sequence, and then dried with anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene intermediate; Step S2: 10 mmol of diene intermediate, 0.3 g of Karstedt catalyst and 100 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 55° C. and the stirring reaction is continued for 30 min. Then, 20 mmol of triethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the stirring reaction is continued for 2 h, and then the mixture is heated to 80° C. and the stirring reaction is continued for 8 h. After the reaction is completed, the reaction product is filtered while hot, and then the filtrate is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain a double-end modified coupling agent; Step S3: 10 g of silicon carbide whiskers with a CAS number of 409-21-2 and an average particle size of 500 nm and 120 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and ultrasonically treated for 2 h at an ultrasonic frequency of 55 kHz, and then adjusted to pH 9 with 25% ammonia water, and then stirred for 15 min at a temperature of 30 ° C and a stirring rate of 400 r / min, and then heated to 75 ° C. The reaction was continued under stirring for 15 minutes, and then 25 mL of a double-end modified coupling agent solution formed by dissolving the double-end modified coupling agent in anhydrous ethanol at a ratio of 2.8 g:10 mL was added dropwise while stirring, and the drop rate was controlled to be 2 drops / s. After the dropwise addition was completed, the reaction was continued under stirring for 8 hours. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 55°C for 5 hours to obtain a modified whisker reinforcing agent. Step S4: 90 parts of ABS resin with a model number of ABS PA-757K, 7.5 parts of modified whisker reinforcing agent, 8 parts of dioctyl terephthalate, 0.3 parts of calcium stearate, 0.5 parts of vinyl bisstearic acid amide and 0.11 parts of antioxidant with a model number of antioxidant 1010 are weighed according to weight parts and set aside; Step S5: adding ABS resin, modified whisker reinforcing agent, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stirring and mixing for 40 minutes at a temperature of 50° C. and a stirring rate of 400 r / min to obtain a mixture; Step S6: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220° C., zone 2 to 230° C., zone 3 to 230° C., zone 4 to 240° C., zone 5 to 240° C., and zone 6 to 245° C., and melt-extrude the mixed material at a screw speed of 120 r / min, and obtain wire pellets after cooling, drying, and pelletizing; Step S7: adding the wire pellets into a single screw extruder, and extruding the wire pellets at a temperature of 240° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.75 mm.
[0025] The graphene-modified ABS nanowires for 3D printing of Examples 1-3 and Comparative Examples 1-4 were tested for tensile strength according to GB / T 1040-1992, tested for bending strength according to GB / T 1042-1979, and tested for thermal conductivity using a thermal constant analyzer. The test results are shown in the following table:
[0026] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the graphene-modified ABS nanowire for 3D printing of the present application has excellent mechanical properties and thermal conductivity.
[0027] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0028] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined in this application, they shall all fall within the protection scope of the present invention.
Claims
1. A graphene-modified ABS nanowire for 3D printing, characterized in that: It comprises the following components in parts by weight: 85-90 parts of ABS resin, 0.5-7.5 parts of nanographene-coated whisker reinforcing agent, 2-8 parts of dioctyl terephthalate, 0.1-0.3 parts of calcium stearate, 0.3-0.5 parts of vinyl bisstearic acid amide and 0.07-0.11 parts of antioxidant; Wherein, the nanographene-coated whisker reinforcing agent is prepared by the following steps: Step s1: stirring eugenol, sodium hydroxide and deionized water for reaction, then adding succinyl chloride solution dropwise and continuing stirring for reaction, after the reaction is completed, allowing the reaction product to stand for separation, washing, drying and rotary evaporating the organic phase to obtain a diene intermediate; Step s2: stirring the diene intermediate, Karstedt catalyst and anhydrous toluene to react, then adding triethoxysilane dropwise and continuing the stirring reaction, filtering the reaction product while hot after the reaction is completed, and then rotary evaporating the filtrate to obtain a double-end modified coupling agent; Step s3: stirring graphite powder and concentrated sulfuric acid for reaction, then adding sodium nitrate, potassium permanganate and deionized water and continuing stirring the reaction, cooling the reaction product after the reaction is completed, then pouring it into a hydrogen peroxide solution, and then centrifuging it, washing and drying the precipitate to obtain nano graphene oxide; Step s4: subjecting nano-graphene oxide, silicon carbide whiskers and deionized water to ultrasonic treatment, adjusting the pH and reacting with stirring, then adding the double-end modified linker solution dropwise and continuing the stirring reaction, cooling the reaction product after the reaction is completed, and then washing and drying to obtain a nano-graphene-coated whisker reinforcement.
2. The graphene-modified ABS nanowire for 3D printing according to claim 1, characterized in that: The usage ratio of the eugenol, sodium hydroxide, deionized water and succinyl chloride solution in step s1 is 20-25 mmol: 25-30 mmol: 40-50 mL: 20-22 mL.
3. The graphene-modified ABS nanowire for 3D printing according to claim 1, characterized in that: The succinyl chloride solution in step s1 is a solution formed by dissolving succinyl chloride in ethyl acetate at a ratio of 10 mmol:20 mL.
4. The graphene-modified ABS nanowire for 3D printing according to claim 1, characterized in that: The usage ratio of the diene intermediate, Karstedt catalyst, anhydrous toluene and triethoxysilane in step s2 is 10 mmol: 0.1-0.3 g: 80-100 mL: 20 mmol.
5. The graphene-modified ABS nanowire for 3D printing according to claim 1, characterized in that: The usage ratio of the graphite powder, concentrated sulfuric acid, sodium nitrate, potassium permanganate and deionized water in step s3 is 3g:100-120mL:2-3g:13-15g:90-100mL.
6. The graphene-modified ABS nanowire for 3D printing according to claim 1, characterized in that: The mass fraction of the concentrated sulfuric acid in step s3 is 98%; the mass fraction of the hydrogen peroxide solution is 25-30%.
7. The graphene-modified ABS nanowire for 3D printing according to claim 1, characterized in that: The dosage ratio of the nano-graphene oxide, silicon carbide whisker, deionized water and double-end modified linker solution in step s4 is 0.8-3.6 g: 10 g: 100-120 mL: 20-25 mL.
8. The graphene-modified ABS nanowire for 3D printing according to claim 1, characterized in that: The silicon carbide whisker in step s4 has a CAS number of 409-21-2 and an average particle size of 100-500 nm; the double-ended modified linker solution is a solution formed by dissolving the double-ended modified linker in anhydrous ethanol at a ratio of 1.2-2.8 g:10 mL.
9. A method for preparing graphene-modified ABS nanowires for 3D printing according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: weigh 85-90 parts of ABS resin, 0.5-7.5 parts of nanographene-coated whisker reinforcement, 2-8 parts of dioctyl terephthalate, 0.1-0.3 parts of calcium stearate, 0.3-0.5 parts of vinyl bisstearamide and 0.07-0.11 parts of antioxidant according to weight parts, and set aside; Step 2: Add ABS resin, nanographene-coated whisker reinforcement, dioctyl terephthalate, calcium stearate, vinyl bisstearamide and antioxidant into a mixer, stir and mix for 30-40 minutes at a temperature of 40-50° C. and a stirring rate of 300-400 r / min to obtain a mixture; Step 3: adding the mixed material into a twin-screw extruder, controlling the temperature of zone 1 to 220°C, zone 2 to 230°C, zone 3 to 230°C, zone 4 to 240°C, zone 5 to 240°C and zone 6 to 245°C, and melt-extrude at a screw speed of 80-120r / min, and obtain wire pellets after cooling, drying and pelletizing; Step 4: Add the wire pellets into a single screw extruder and extrude them at a temperature of 220-240° C. to prepare graphene-modified ABS nanowires for 3D printing with a diameter of 1.70-1.75 mm.
10. The method for preparing graphene-modified ABS nanowires for 3D printing according to claim 9, characterized in that: The model of the ABS resin is ABS PA-757K; the model of the antioxidant is one of antioxidant 1076, antioxidant 1035 and antioxidant 1010.
Citation Information
Cited By
Continuous long fiber 3D printing ABS filament, and preparation method and application thereof
CN122686061A